Synthesis, Optical Properties, and DNA Interaction of New Diquats Based on Triazolopyridines and Triazoloquinolines. Issue 52 (16th August 2017) - Llabres‐Campaner, Pedro J.; Guijarro, Lluís; Giarratano, Claudia; Ballesteros‐Garrido, Rafael; Zaragozá, Ramón J.; Aurell, M. José; García‐España, Enrique; Ballesteros, Rafael; Abarca, Belén
Abstract: New diquat derivatives based on [1, 2, 3]triazolo[1, 5‐ a ]pyridine and [1, 2, 3]triazolo[1, 5‐ a ]quinoline have been synthesized in excellent yields. To evaluate the effect of the alkyl bridge length, ethane and propane dibromo alkane substrates were used for their synthesis. Theoretical calculations predicted a very small energetic barrier between the two possible enantiomers P ( Ra ) and M ( Sa ), which makes them very difficult to resolve. Thermal denaturation studies, UV/Visible spectroscopy, and fluorescence titrations with ct‐DNA evidenced the intercalation of the quinoline derivatives in DNA. Abstract : Electrostatic interactions : New diquat derivatives based on [1, 2, 3]triazolo[1, 5‐ a ]pyridine and [1, 2, 3]triazolo[1, 5‐ a ]quinoline have been synthesized in excellent yields. To evaluate the effect of the alkyl bridge length, ethane and propane dibromo alkane substrates were used for their synthesis (see scheme).